Influence of East Asian winter monsoon on particulate matter pollution in typical regions of China. (1st September 2021) - Li, Yanjun; An, Xingqin; Zhang, Peiqun; Yang, Jianling; Wang, Chao; Li, Jiangtao
Abstract: This study uses the NCEP/NCAR monthly average reanalysis and number of haze day data during 1958–2017, and the average daily PM2.5 mass concentration data during 2013–2017, to calculate the East Asian winter monsoon index (EAWMI) and statistically analyze the correlation between the winter monsoon index and air quality in China, particularly for the five typical regions (Beijing-Tianjin-Hebei, Fen-Wei Plain, Sichuan-Chongqing Delta, Yangtze River Delta, and Pearl River Delta). Thereafter, the strong and weak winter monsoon years were classified based on the EAWMI, and the atmospheric circulation and temperature fields over China and the five regions in different winter monsoon years were spatially compared. Finally, the study also investigated the various distribution features of the climatic circulation background responsible for the strong and weak winter monsoons and their impact mechanisms on air quality the five typical regions in China. The results show that the effect of the winter monsoon on the air quality of China may be represented by a north–south boundary line located at approximately 30° N. During strong winter monsoon years, pollution was lower in the area north of the boundary but higher to its south. By contrast, the opposite phenomenon was observed during the weak monsoon years. During the strong winter monsoon years, the Beijing-Tianjin-Hebei region and Fen-Wei Plain to the north of the boundary line were less polluted, while the Yangtze River, Chengdu-Chongqing, and Pearl River delta regions to the south of the boundary were more polluted. Diagnostic analysis of the circulation field indicated that during the strong winter monsoon years, an abnormal downward airflow occurred to the south of the boundary, limiting convective diffusion and thereby causing the increased pollution. However, during the weak winter monsoon years, ascending airflows occurred, which favored pollutant diffusion. Furthermore, during the strong winter monsoon years, an abnormal southeast airflow with weak horizontal wind speed occurred in the lower atmosphere of the Chengdu-Chongqing region, causing localized pollutant accumulation, thereby aggravating the pollution. In the Pearl River Delta region, a descending abnormal westerly flow inhibited the local uplift and diffusion of air. Moreover, importing pollutants occurred from the north, aggravating the pollution in the region. Highlights: The correlation between East Asian winter monsoon and air pollutants in regions China were statistically analyzed. The air quality has different distribution in strong and weak winter monsoon year between the dividing line around 30°N. The different distribution features of the climatic circulation responsible for strong and weak winter monsoons were compared. Analyzed the influence mechanism of the strong and weak winter monsoon climate circulation on the air quality in China.